Upaya Memahami Mindfullness untuk Mendorong Kreativitas Siswa Songsreem Sasana Vitaya, Hatyai, Thailand - Hardani Widhiastuti; Rusmalia Dewi; Sarah Wanlabeh (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This international community service was conducted at Songsreem Sasana Vitaya, Hatyai, Thailand which aims to provide training with the theme of Mindfullness to improve student creativity. The problem that often occurs is that to motivate student creativity there is no curriculum that specifically supports children's creativity. Moreover, students equivalent to high school prioritize emotional souls which are sometimes not accompanied by positive creativity. Age is one of the considerations, considering that high school age is an age that prioritizes spontaneity or what is desired. Sometimes ideals have not been described by them. The method of this activity is in the form of training on Mindfullness to support this creativity, the method is training that takes almost 3 hours, which is attended by around 75 students and 5 teachers and 1 principal. The results obtained in the form of descriptive qualitative by explaining and describing the conditions of participants who participated in this activity with pleasure and enthusiasm, considering that this is the first activity to be followed and carried out by higher education institutions from Indonesia. The end of this activity was closed with relaxation.